Assessment of Recovery Time, Worsening, and Death among Inpatients and Outpatients with COVID-19, Treated with Hydroxychloroquine or Chloroquine plus Azithromycin Combination in Burkina Faso. (May 2022) - Rouamba, Toussaint; Ouédraogo, Esperance; Barry, Houreratou; Yaméogo, Nobila Valentin; Sondo, Apoline; Boly, Rainatou; Zoungrana, Jacques; Ouédraogo, Abdoul Risgou; Tahita, Marc Christian; Poda, Armel; Diendéré, Arnaud Eric; Ouedraogo, Abdoul-Salam; et al.
Highlights: Hydroxychloroquine + azithromycin (HCQ + AZ) did not reduce recovery time in COVID-19 HCQ + AZ had no effect on the risk of worsening or transfer to the intensive care unit The use of HCQ + AZ appeared to be associated with lower mortality rates Abstract: Objectives: Our study aimed to assess the statistical relationship between the use of chloroquine phosphate or hydroxychloroquine plus azithromycin (CQ/HCQ + AZ) and virological recovery, disease worsening, and death among out- and inpatients with COVID-19 in Burkina Faso. Methods and Designs: This was a retrospective observational study that compared outcomes in terms of time to recovery, worsening, and death in patients who received CQ/HCQ + AZ and those who did not using a multivariable Cox or Poisson model before and after propensity matching. Results: Of the 863 patients included in the study, about 50% (432/863) were home-based follow-up patients and 50% were inpatients. Of these, 83.3% (746/863) received at least 1 dose of CQ/HCQ + AZ and 13.7% (118/863) did not. There were no significant differences in associated time to recovery for patients receiving any CQ/HCQ + AZ (adjusted HR 1.44; 95% CI 0.76–2.71). Similarly, there was no significant association between CQ/HCQ + AZ use and worsening (adjusted IRR 0.80; 95% CI 0.50–1.50). However, compared with the untreated group, the treated group had a lower risk of death (adjusted HR 0.20; 95% CI 0.10–0.44). Conclusions: The study provided valuable additional information on the use of CQ/HCQ in patients with COVID-19 and did not show any harmful outcomes of CQ/HCQ + AZ treatment.